Vitamin B12 and proton pump inhibitors - Sutkowski, Michał (Lekarz POZ, 2025)
Vitamin B12 deficiency may be associated with significant hematologic, neurologic, psychiatrics and gastrointestinal abnormalities. One of the important reasons in the widespread, sometimes excessive, use of proton pump inhibitors (PPIs). The cause of vitamin B12 deficiency should be identified and treated, and PPI therapy should be rationalized accordingly.